The efficacy of upfront craniocerebral radiotherapy and epidermal growth factor receptor-tyrosine kinase inhibitors in patients with epidermal growth factor receptor-positive non-small cell lung cancer with brain metastases - Zhou, Jianxi; Zhou, Yingnan; Sun, Yunchuan; Xiao, Li; Lu, Hongling; Yin, Xiaoming; Fan, Kui (Frontiers in Oncology, 2024)
The present study aims to investigate the therapeutic value of third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) combined with cranial radiotherapy (RT) in patients with EGFR-positive non-small cell lung cancer (NSCLC) and brain metastases (BMs). Methodology: This is a retrospective study that involved 213 patients with EGFR-NSCLC and BMs, with the patients divided into two groups: the upfront cranial RT (ucRT) group (n = 96) and the non-ucRT group (n = 117). All patients were administered with osimertinib, and those in the ucRT group also underwent RT. The overall survival (OS), progression-free survival (PFS) and intracranial PFS (IPFS) of the two groups were compared. Results: The ucRT group manifested a markedly higher IPFS than the non-ucRT group (29.65 months vs 21.8 months; P < 0.0001). The subgroup analysis revealed that patients with oligometastases (OLOGO-BMs; 1–3 BMs) demonstrated a notably longer OS (44.5 months vs 37.3 months; P < 0.0001), PFS (32.3 months vs 20.8 months; P = 0.6884) and IPFS (37.8 months vs 22.1 months; P < 0.0001) in the ucRT group than in the non-ucRT group. However, for patients with multiple BMs, there was no significant difference in OS (27.3 months vs 34.4 months; P = 0.0710) and PFS (13.7 months vs 13.2 months; P = 0.0516) between the ucRT group and the non-ucRT group; the ucRT group exhibited a higher IPFS (26.4 months vs 21.35 months; P = 0.0028). Cox’s multivariate analysis of patients with OLOGO-BM indicated that the use of ucRT was linked to a better OS (heart rate [HR] = 0.392; 95% confidence interval [CI]: 0.178–0.863; P = 0.020) and PFS (HR = 0.558; 95% CI: 0.316–0.986; P = 0.044). Conclusion: Upfront cerebral cranial stereotactic radiosurgery can improve outcomes in EGFR-positive patients with NSCLC and OLOGO-BM. However, for patients with multiple BMs, the preferable strategy may be pre-treatment with EGFR-TKIs.